Optical correlation technique for cement particle size measurements - Gorsky, Mykhaylo P.; Maksimyak, Peter P.; Maksimyak, Andrew P. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
Optical correlation technique of determining the cement particle size distribution is described. It is based on transverse coherent function measurement using a polarization transverse shearing interferometer. The proposed technique of data processing decreases the dependence of the result on interferometer noise, emission source intensity fluctuations and difference of refractive index magnitudes of different cement particles. The technique allows fast and reliable determination of the size distribution function of cement particles.
Optica Applicata, Vol. 40, 2010, nr 2, s. 459-469
Keywords: optyka; transverse coherence; polarization interferometer; cement; size distribution function